Optimalisasi Program Magang untuk Meningkatkan Kreativitas dan Inovasi Mahasiswa - Tiur Malasari Siregar; Fajar Apollo Sinaga; Taufiq Ramadhan; Kana Saputra; Elfitra Elfitra; Yul Ifda Tanjung; Tangsi Tangsi (Universitas Indraprasta PGRI, 2026)
creativity and innovation so that graduates are better prepared to compete in the job market. This study aims to evaluate the effectiveness of the internship program at Medan State University and develop optimization strategies that focus on enhancing student creativity and innovation. This study was conducted using a mixed-method approach, namely a qualitative approach through interviews with students and industry representatives and observation. The quantitative approach through surveys and tests of student performance in the internship program. The research subjects included students and several partner companies where students underwent internships. The results showed that students involved in the internship program with an innovative project-based approach had higher levels of creativity compared to students who only carried out administrative tasks. Factors contributing to the program's success included the involvement of industry mentors, the integration of a problem-solving-based curriculum, and support facilities that foster innovation. The novelty of this research lies in the development of a creativity- and innovation-based internship program optimization model, which has not yet been widely implemented in Indonesian universities. This contributes to academic policy by improving the effectiveness of internship programs and strengthening university-industry collaborations to produce graduates better prepared to compete in the digital age.